Perbedaan indeks plak antara yang menyikat gigi menggunakan pasta gigi herbal dan non herbal pada mahasiswa Poltekkes Kemenkes Padang - Ifitri, Ika; Warman, Anses; Arnetty, Arnetty; Oktaviani, Fitrisia; Amiruddin, Amiruddin (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Dental and oral health issues are influenced by various factors, one of which is plaque formation. Controlling plaque can be achieved through mechanical and chemical means, such as brushing with toothpaste that contains ingredients capable of inhibiting plaque growth.Objectives: This study aimed to examine differences in plaque index among students who brushed their teeth using herbal versus non-herbal toothpaste at the Dental Health Department, Padang Health Polytechnic, Ministry of Health.Methods: Employing a quasi-experimental design with a post-test group approach, this research included 71 third-year students from the department. The study measured plaque indices after brushing with either herbal or non-herbal toothpaste. Data analysis involved univariate and bivariate methods, with the Independent T-Test used for bivariate analysis.Results: Findings revealed that the average plaque index was 0.3 in the herbal toothpaste group and 0.4 in the non-herbal group. Statistical testing showed a ρ value of 0.02 (0.02 < 0.05) and a mean difference in plaque index of -1.04.Conclusion: This indicates a significant difference between the two groups, with herbal toothpaste showing a more favorable effect on plaque reduction.